Chemical constituents and biological activities of South East Asia marine sponges: a review - Lee, Kah Nyan; Abas, Faridah; Maulidiani; Ahmed, Mediani; Leong, Sze Wei; Ismail, Intan Safinar; Shaari, Khozirah (Universiti Putra Malaysia Press, 2019)
The ocean has an exceptional resource with various groups of natural products that are potentially useful for biomedical and other applications. Marine sponges have prominent characteristic natural products with high diversity. They produce many vital therapeutic metabolites with prominent biological activities. Marine invertebrates and microbial communities are the primary producers of such metabolites. Among the richest sources of these metabolites, class Demospongiae and the order Haplosclerida and genus Xestopongiae from family Petrosiidae are of interest. This review summarizes the research that has been conducted on two classes, eight orders, twelve families and fourteen genera of marine sponges available in the South East Asia region, covering the literature of the last 20 years. Ninety-five metabolites including alkaloids, sterols, terpenoids, quinones isolated from marine sponges collected in South East Asia along with their bioactivities especially cytotoxicity and antibacterial activities were reported in this review. Chemistry and biology are highly involved in studying marine sponges. Thus, tight collaboration is needed for understanding their taxonomy aspects. This review will outline chemistry and biological aspects, challenge, limitation, new idea and a clear future perspective on the discovery of new drugs from South East Asia's marine sponges.